1991
DOI: 10.1016/0092-8674(91)90182-x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of the cell cycle through mitosis leads to abortion of nascent transcripts

Abstract: SummaryNascent transcripts of the Drosophila Ubx gene were detected by in situ hybridization. Following onset of expression, the progress of RNA polymerase (1.4 kb/min) across the gene was visualized as the successive appearance of hybridization signals from different positions within the transcription unit. Nascent transcripts disappeared at mitosis. Hybridization signals reappeared in the next cell cycle first with a 5′ probe, and later, following a delay consistent with the transcription rate, with a 3′ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
295
3
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 368 publications
(314 citation statements)
references
References 30 publications
15
295
3
1
Order By: Relevance
“…While atomistic modeling is arguably (62,63) the only method available at the moment that can deliver the transient PANS at full atomic resolution, the method (64) cannot yet probe timescales of seconds relevant to key biological processes such as transcription (65), which depend critically on the DNA packing in the nucleosome. Here, the difficulty is overcome by verifying experimentally that the key geometric characteristics of the modeled structures, including the length of protected DNA, remain close to the observed values on the AFM timescales of minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While atomistic modeling is arguably (62,63) the only method available at the moment that can deliver the transient PANS at full atomic resolution, the method (64) cannot yet probe timescales of seconds relevant to key biological processes such as transcription (65), which depend critically on the DNA packing in the nucleosome. Here, the difficulty is overcome by verifying experimentally that the key geometric characteristics of the modeled structures, including the length of protected DNA, remain close to the observed values on the AFM timescales of minutes.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, characteristic timescales for spontaneous DNA unwrapping deep inside the nucleosome can reach 10 min, and possibly even longer for sites further away from the entry/exit (10). This very slow unwrapping kinetics undoubtedly reduces the speed of Pol II machinery considerably-unimpeded, the latter can transcribe the entire nucleosomal DNA in seconds (65).…”
Section: Relevance To Dna Accessibility Controlmentioning
confidence: 99%
“…We think the same pros protein is moving from the GMC cortex into the nucleus, because the process occurs too rapidly for de novo synthesis of new pros in the GMC. The pros gene is >23 kb (data not shown), and would take over 20 minutes to transcribe and translate (Thummel et al, 1990;Shermoen and O'Farrell, 1991); we observe nuclear localization rapidly after mitosis (see Results). However, it is possible that pros RNA is inherited by the GMC and could be rapidly translated and localized to the nucleus.…”
Section: Mechanisms Of Asymmetric Prospero Localizationmentioning
confidence: 96%
“…Nascent Ultrabithorax transcripts are aborted as cells pass through mitosis 3 , reappearance of completed transcripts in the next cell cycle being delayed by the 55 minutes required for the task. In cells that initiate transcription of Ultrabithorax too late in the cell cycle, the arrival of mitosis prevents completion of transcripts.…”
Section: Tempomentioning
confidence: 99%
“…The mammalian RNA polymerase working at its rate of about 3 kilobases (kb) per minute (37 °C) requires roughly 11 hours to traverse the gargantuan (2,000-kb) dystrophin gene. Measurements 2,3 of the lag between initiation at a promoter and transcription of downstream sequences have shown that the Drosophila polymerase progresses at about 1.4 kb per minute (25 °C). At this rate, 55 minutes are required for transcription of the Ultrabithorax gene, whereas only 2 are needed for the shorter knirps gene.…”
mentioning
confidence: 99%